(untitled) (Journal of Plant Disease Sciences, 2021)
During the Rabi season of 2019-20, a field experiment was conductedat the Pulses Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola, Maharashtra, India to study the tillage management in chickpea (Cicer arietinum L.) under mungbean- chickpea crop sequence. Result indicated that highest root length (12.42 and 14.82cm at flowering and pod development respectively), number of root nodules/plant(31.20 and 15.30 root nodules / plant at flowering and pod development, respectively) and dry weight (0.37 and 0.29mg at flowering and pod development, respectively) of root nodules were recorded with treatment tractor drawn cultivator + harrowing + sowing + one hoeing + one hand weeding. Theinfluence of varieties on root length, root nodules/ plant, dry weight of root nodules was found non-significant. Soil microbial population of chickpea crop increased with tillage treatment application of glyphosate immediately after the harvest of mungbean + sowing. However, there was no significant effect of tillage treatments on Fusarium wilt.